Modified Cervicofacial Flap for Large Cheek Defect Reconstruction under Local Anesthesia - Shiv Prasad Sharma; Akshay Nigam (Case Reports in Surgery)
The cervicofacial flap was first described in 1969. For the past several years, it has been the flap of choice for the reconstruction of facial defects especially cheek defects. In recent years, with the advent of microvascular free flap tissue transfer, the use of a cervicofacial flap has been sparse. This article highlights the importance and application of locoregional flaps such as a cervicofacial flap in the reconstruction of soft tissue defects on a face. This case was unique from the reconstruction point of view. An 81-year-old patient presented to us with a long standing ulcerated growth in his left cheek which was neglected due to lack of symptoms and his poor financial condition. Clinically, the extent was defined from the suborbital skin region till the mid cheek region and medially from the lateral nasal crease up to the cheek prominence area. An initial biopsy suggested basal cell carcinoma. The lesion was excised, and a 4.5×5.5 cm defect was reconstructed using a modified “cervicofacial” flap under local anesthesia. Our experience shows that this technique is a reliable, easy to harvest flap with good outcomes. Moreover, it can be utilized in those candidates not suitable for a free flap procedure under general anesthesia.